Integrating “storytelling” as a method in judicial processes? - Filip Strandberg Hassellind (Oñati Socio-Legal Series)
This paper examines how Colombia’s Justicia Especial para la Paz (JEP) emerges as a tribunal within which the roles of history, politics, and transitional justice becomes contested. The paper starts by placing the JEP in a historical, social, and political context. Building on the contextualization, it focuses on how the JEP appears to be an extension of the five-decade long conflict in Colombia in its attempt to deal with the past. The paper underscores how punishing “bad” things is not an easy task. Against this background, the paper challenges the boundaries of criminal liability by discussing and analyzing “storytelling” as an alternative to truth-telling in the JEP in order to not only provide additional nuances to the conflict, but also as a way to, at least theoretically, tie different social collectives together in a post-conflict society and enable the courtroom to function constructively with difficult social issues in the aftermath of cataclysm.